Socially Engaged Arts (SEA) Practices : Key Skills and Capabilities - Lehikoinen, Kai; Siljamäki, Eeva (Aalto-yliopisto, 2023)
Socially engaged arts (SEA) have evolved in multiple directions, creating new competence needs for practitioners. This article investigates SEA as a professional practice to enhance it as a field of study in higher arts education. An inductive qualitative approach is applied to analyze extant curricula, literature, and interviews to grasp how the key competences are discussed in the practitioner, educational, and scholarly contexts to identify and structure eight competence areas practitioners can benefit from. The article contributes to a deeper understanding of the changing landscape of artists’ professionalism and the potential of higher arts education in supporting artists in SEA.
Keywords: taidekasvatus; osaaminen; taide; yhteisötaide; korkea-asteen koulutus